Level of Modernization among School Teachers Belonging to Tribal Community: A Study on the Modernization Levels of Tribal School Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study has been conducted to find out the Levels of modernization among school teachers belonging to tribal community. The sample for the investigation was drawn from the school teachers belonging to tribal community working in different schools located in Ranga Reddy district, Telangana state by using simple random sampling techniques. It comprises 310 school teachers. Standardized tools were used in the present study. Comprehensive Modernization Inventory (CMI) developed by Ahluwalia S.P. and Kalia A.K. The results of the present study revealed that here is no significant difference between Levels of modernization among school teachers belonging to tribal community on the respect of their gender, age, and Marital Status and Educational qualification.